Metode Bimbingan Manasik Haji pada PT. Grand Darussalam - Hafidz, Abdul; Fadli, Fadli; Jasmine, Cinta Aurel; Rahmadhani, Najwa Gusty (LANCAH: Jurnal Inovasi dan Tren, 2024)
The Hajj ritual guidance method is a way toResolving problems during the The hajj manasik guidance method is a way to solve problems in the hajj" can be interpreted as "The hajj manasik guidance method is a strategy to overcome problems that arise in the implementation of the hajj. In this method, it is stated that the understanding of the implementation of Hajj which will make it easier for prospective pilgrims in the future" can be interpreted as "The method teaches an understanding of the implementation of Hajj, so that prospective pilgrims can undergo Hajj more easily in the future. In this study, the author uses descriptive (qualitative) research" can be interpreted as "The author uses a descriptive research approach that has qualitative characteristics. The formulation of the problem in this study is how the method of guidance for hajj manasik in increasing the knowledge of pilgrims at PT Grand Darussalam.The results of this study can be concluded that the hajj manasik guidance method implemented by PT Grand Darussalam can be interpreted as the hajj manasik guidance method applied by PT Grand Darussalam.